Android malware detection using network traffic based on sequential deep learning models. (6th June 2022) - Fallah, Somayyeh; Bidgoly, Amir Jalaly
Abstract: The increasing trend of smartphone capabilities has caught the attention of many users. This has led to the emergence of malware that threatening the users' privacy and security. Many malware detection methods have been proposed to deal with emerging threats. One of the most effective ones is to use network traffic analysis. This article proposed a method based on LSTM (Long Short‐term Memory) for malware detection which is capable of not only distinguishing malware and benign samples, but also detecting and identify the new and unseen families of malware. As far as we know, this is the first time that traffic data has been modeled as a sequence of flows and a sequential based deep learning model is employed. In this article, we have performed several case studies to exhibit the capabilities of the proposed method including malware detection, malware family identification, new (not seen before) malware family detection, as well as evaluating the minimum time required to detect malware. The case studies show that the model is even capable of detecting new families of malware with more than 90% accuracy, although these results can only be verified on existing families in this dataset and such a claim cannot be generalized to other examples of malware. Moreover, it is shown the model is able to detect the malware through capturing 50 connection flows (about 1600 packets in average) with the AUC of more than 99.9%.